Natural Flavonoid Pectolinarigenin Alleviated Hyperuricemic Nephropathy via Suppressing TGFβ/SMAD3 and JAK2/STAT3 Signaling Pathways - Ren, Qian; Wang, Bo; Guo, Fan; Huang, Rongshuang; Tan, Zhouke; Ma, Liang; Fu, Ping (Frontiers in Pharmacology, 2022)
Natural flavonoid pectolinarigenin (PEC) was reported to alleviate tubulointerstitial fibrosis of unilateral ureteral obstruction (UUO) mice in our previous study. To further investigate nephroprotective effects of PEC in hyperuricemic nephropathy (HN), adenine and potassium oxonate induced HN mice and uric acid-treated mouse kidney epithelial (TCMK-1) cells were employed in the study. As a result, PEC significantly lowered serum uric acid level and restored hyperuricemia-related kidney injury in HN mice. Meanwhile, PEC alleviated inflammation, fibrosis, and reduced adipokine FABP4 content in the kidneys of HN mice and uric acid-treated TCMK-1 cells. Mechanistically, PEC inhibited the TGF-β1 expression as well as the phosphorylation of transcription factor SMAD3 and STAT3 to regulate the corresponding inflammatory and fibrotic gene expression in kidney tissues. In conclusion, our results suggested that PEC could inhibit the activation of SMAD3 and STAT3 signaling to suppress inflammation and fibrosis, and thereby alleviate HN in mice.